Project Cost Escalation Prediction Models Based on System Dynamics Approach - Wisnu Broto, Y. Suponco; Adi, Tri Joko Wahyu; Suryani, Erma; Soetjipto, Jojok Widodo (IPTEK Journal of Proceedings Series, 2017)
Multiyear construction project is one of the riskiest project due to uncertainty and dynamic economic condition. In multi-years project, cost escalation is inevitable because during construction period various risk factors such as increasing of labor cost, materials cost, energy cost, and equipment cost will affect the costs of the projects. This paper proposes a model to estimate cost escalation based on System Dynamic (SD) approach. SD is used to represent correlation among risk factors influencing cost escalation and to calculate cost escalation during project period. Causal Loop Diagram (CLD) was made based on in-depth literature review and confirmed by the experts. To validate the model, 7 multi-years projects in Indonesia were used as case study. The result showed that the proposed model can accurately predict project cost escalation with an accuracy of 91.21%. Simulation of SD also showed that the change of scope of work, ambiguous contract condition, unpredictable conditions, project schedule delay, inflation, and extreme weather condition are the most influencing factor of cost escalation. Besides predicting cost escalation of project, this model can also be used as early warning system in multi-year projects environment.